Prescription pattern of antimicrobials in pregnant women attending antenatal clinic in a tertiary care hospital in Telangana, India - Begum, Md. Amirunnisa; Sowmya, B. Krishna; Shailendra, D. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pregnancy is a physiological condition during which immune system is weakened. Therefore, most women are prone to develop infections during this period for which antimicrobials are prescribed. Drugs used during pregnancy may lead to teratogenicity. Therefore, this study was done with the following objectives: 1.to determine the type of infections encountered, 2.to assess the prescription profile of antimicrobials and 3.to assess FDA categories of antimicrobials used in pregnant women in a tertiary care center in Telangana, India. Methods: This was a prospective observational study conducted on pregnant women attending antenatal clinic (ANC) at Mediciti Institute of Medical Sciences (MIMS) from 1st January 2018 to 30th June 2018. Results: Out of a total of 165 cases enrolled, 57 (34.5%) cases were prescribed antimicrobials and 108 (65.5%) were treated symptomatically. The mean (SD) age of women who were prescribed antimicrobials was 22.9 (2.97) years. Of the conditions encountered, respiratory tract infections (RTIs) accounted for 31%, followed by urinary tract infections (UTIs) 26% and gastroenteritis 25%. Most prevalent infections which required antimicrobials prescription were UTIs (36.84%), followed by Gastroenteritis (17.54%). Majority of the antimicrobials prescribed were from Betalactams (40.34%), followed by Nitrofuranes (29.82%), Nitroimidazoles (17.54%) and Antifungals (8.77%). Antimicrobials prescription was more in the 3rd trimester (63.1%), followed by 2nd trimester (31.6%) and 1st trimester (5.3%). Majority of the antimicrobials were administered orally (75.44%), followed by injections (15.79%) and per vaginal route (8.77%). Antimicrobials were mostly prescribed from FDA Category B (96%). Conclusions: RTIs were the most common among the conditions encountered. However, UTIs were the leading cause for antimicrobial prescriptions. Antimicrobials prescription was more during 3rd trimester. Most antimicrobials prescribed were safe as they were from FDA Category B.